Inteligência emocional e autopercepção do desempenho de atletas universitários em uma competição - Souza, Lucas Cordeiro Inácio (Universidade Federal de São Carlos, 2025)
Emotional intelligence (EI) is a psychological construct that encompasses the capacities for emotional perception, emotional facilitation of thought, emotional understanding, and emotional management. EI is present in a wide variety of contexts, such as competitive sports. However, there is little literature on EI in university sports, whose athletes have greater psychological needs compared to professionals. The objective of this study, therefore, was to evaluate emotional aspects and skills of university athletes before and after a competition. The sample consisted of 37 athletes from individual sports in a university athletic association. Four data collections were carried out at different times, from preparation to post-competition, in which the following were evaluated: emotional understanding; sociability; positive and negative affect; and emotional regulation, variables that were related to self-perception of performance in sports and actual performance. The results were analyzed using descriptive statistics and repeated measures ANOVA. Additionally, Spearman's correlation test was performed to verify the level of association between the psychological constructs and the two performance variables in the competition, as well as a network analysis. The findings indicate that the presence of negative affect is more impactful on athletic performance than positive affect. Furthermore, a tendency was found for individuals with more negative affect to evaluate themselves negatively and lose the competition. Finally, emotional intelligence and sociability were shown to have an indirect influence on performance, potentially acting as a mitigator of negative affect, without overriding technical and infrastructural factors in sports.
Emotional intelligence and self-perception of performance among university athletes in a competition
Keywords: inteligência emocional; esporte universitário; avaliação psicológica; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA::CONSTRUCAO E VALIDADE DE TESTES, ESCALAS E OUTRAS MEDIDAS PSICOLOGICAS; 3. Saúde e Bem-Estar